RESEARCH OF HOT-SETTING PHENOL-ALDEHYDE CONNECTIVE IN CARBON COMPOSITES - Skachkov , Viktor; Vodennikov , Sergey; Berezhnaya , Olga; Nesterenko , Tatiana; Volyar , Roman (Scientific Journal "Metallurgy", 2020)
Theoretical and experimental researches of process of hot-setting phenol-formaldehyde connective are executed in carbon compos. Kinetic equalizations over are brought, taking into account the phenomena of autobraking and autoacceleration of processes of hot-setting and the methods of determination of parameters of the indicated equations are offered. The construction of model of solidifiability of phenol-formaldehyde of astringent taking into account processes autoacceleration and autobraking is considered. An experimental way is set treason of the dynamic module of resiliency and mass losses during the solidifiability of phenolformaldehyde astringent on conditions of stationary temperature. Possibility of calculation-experimental determination of constant of speed of process of solidifiability is shown and quantitative values of parameters of autoacceleration and autobraking. Eventual stage of hot-setting phenol-formaldehyde connective (PFC) characterized by forming of three-dimensional net which provides viscoelastic and resiliently-plastic descriptions. For determination of вязкоупругих descriptions connective in the process of hot-setting an ultrasonic method was used. The change of speed of passing of the ultrasonic length modes was determined curing sample on the basis of PFC. Dependences of change of viscoelastic descriptions are set depending on time of process of hot-setting of standards in the conditions of isothermal self-control three temperatures 90, 110, 130 and 150 С. On the basis of finding the constants of kinetic equation of process of hot-setting of PFC are certain. In the process of hot-setting there is a decline of mass of PFC due to moving away of low-molecular volatiles. The crooked dependences of change of mass of ФФС are built in the process of isothermal self-control at temperatures 70, 80, 90, 110 and 120 С. On the basis of finding the constants of kinetic equalization of process of hot-setting of PFC are also certain. It is set that constants of kinetic equalization, got on both offered variants coincide and ground for control of process hot-setting of PFC both on the change of rate of passing of ultrasound and on the change of mass of cold-setting standards.